Nouns and pronouns in Central Lembata Lamaholot (Austronesian, Indonesia) - Fricke, Hanna (Wacana, Journal of the Humanities of Indonesia, 2017)
In the past, linguists focused their studies on the description of the varieties of Lamaholot spoken in coastal communities. This article introduces Central Lembata Lamaholot, a Lamaholot variety spoken in the central mountains on the island of Lembata in the Indonesian province Nusa Tenggara Timur (NTT), which possesses features in the nominal and pronominal domains not found in other varieties of Lamaholot described so far. Alienable nouns in Central Lembata have morphological plural and specificity marking, and one sub-set of the alienable nouns has two alternating forms which are functionally different. Furthermore, free and bound pronouns in Central Lembata Lamaholot are intertwined with aspect and mood marking. The comparative analysis of these features of Central Lembata Lamaholot shows that they are partly retentions from an earlier stage of the language and partly internal innovations.